2016
DOI: 10.3389/fmars.2016.00090
|View full text |Cite|
|
Sign up to set email alerts
|

Depth Dependent Relationships between Temperature and Ocean Heterotrophic Prokaryotic Production

Abstract: Marine prokaryotes play a key role in cycling of organic matter and nutrients in the ocean. Using a unique dataset (>14,500 samples), we applied a space-for-time substitution analysis to assess the temperature dependence of prokaryotic heterotrophic production (PHP) in epi-(0-200 m), meso-(201-1000 m) and bathypelagic waters (1001-4000 m) of the global ocean. Here, we show that the temperature dependence of PHP is fundamentally different between these major oceanic depth layers, with an estimated ecosystem-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 64 publications
3
28
1
Order By: Relevance
“…Comparatively, DOC L and DOC SL have lower apparent E a of ∼35-40 and ∼50-70 kJ mol −1 , respectively, which are comparable to values estimated for the degradation of glucose (30 kJ mol −1 ), tannin (70 kJ mol −1 ), labile soil organic matter (∼44 kJ mol −1 ), and values recently predicted for marine respiration (∼56 kJ mol −1 ) and mesopelagic prokaryote production (∼72 kJ mol −1 ) (Knorr et al, 2005;Davidson and Janssens, 2006;Yvon-Durocher et al, 2012;Lønborg et al, 2016). Overall this suggests that the DOC SR pool has higher activation energies and temperature dependence than the DOC L and DOC SL pools.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Comparatively, DOC L and DOC SL have lower apparent E a of ∼35-40 and ∼50-70 kJ mol −1 , respectively, which are comparable to values estimated for the degradation of glucose (30 kJ mol −1 ), tannin (70 kJ mol −1 ), labile soil organic matter (∼44 kJ mol −1 ), and values recently predicted for marine respiration (∼56 kJ mol −1 ) and mesopelagic prokaryote production (∼72 kJ mol −1 ) (Knorr et al, 2005;Davidson and Janssens, 2006;Yvon-Durocher et al, 2012;Lønborg et al, 2016). Overall this suggests that the DOC SR pool has higher activation energies and temperature dependence than the DOC L and DOC SL pools.…”
Section: Discussionsupporting
confidence: 81%
“…More recently, the Arrhenius law has been used for calculating the E a of plankton community metabolism, suggesting that marine autotrophs and heterotrophs might react differently to ocean warming (Yvon-Durocher et al, 2012;Chen and Laws, 2017). It has also been shown that the temperature dependence of heterotrophic prokaryote production is fundamentally different between the upper and deeper layers of the ocean (Lønborg et al, 2016). Dissolved oxygen utilization rates in the ocean, computed from dissolved oxygen concentrations and apparent water age estimates, have also revealed a noteworthy temperature sensitivity of microbial respiration Peltzer, 2016, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis showed temperature dependence of CR in the coral reef and GPP in the open sea ecosystems. These disparate responses to temperature may be related to differences in the supply of nutrients, availability of organic matter, and/or food web community composition and structure (Sarmento et al, 2010;López-Urrutia and Morán, 2015;Lønborg et al, 2016). These results are also slightly at odds with our BRT analysis, where temperature was an important predictor of CR in both coral reef and open sea ecosystems, and was not selected as a predictor of GPP in any.…”
Section: Environmental Determinants Of Metabolismcontrasting
confidence: 58%
“…We quantified the strength of bottom‐up control from the relationship between PHB and PHP (Billen, Servais, & Becquevort, ). By temperature control, we will refer to the thermal sensitivity of the community, which was characterized by the apparent activation energy of PHP (Lønborg et al., ). Finally, we used the mean abundances of heterotrophic nanoflagellates and free viruses as a proxy for top‐down control.…”
Section: Introductionmentioning
confidence: 99%